Investigation of dislocations in Ge single crystals by scanning electron beam - Nadtochy, V.; Golodenko, M.; Moskal, D. (Functional Materials, 2004)
The comparative analysis of the dislocation images obtained by optical and scanning electron microscopy in Ge single crystals has been carried out. The results obtained by both methods agree well with each other. When there is no impurity atmosphere, the etching pit or the image spot on the dislocation is about 1 pm in diameter. By creating an electric field at the semiconductor surface, the spatial charge area around the dislocation can be polarized. A contrast appears around the dislocation when the area is scanned by electron beam. This enables the distinguishing of dislocations created by low-temperature deformation among neutral impurity inclusions in a crystal.